IMPROVING REPUTATION OF ENGLISH LANGUAGE EDUCATION STUDY PROGRAM - FKIP, BATANGHARI UNIVERSITY THROUGH ACCREDITATION - Dian Hasfera; Erisa Kurniati; Ade Marta Putra (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This paper discusses the importance of accreditation in an effort to support increasing the reputation of an English Language Education Study Program, at the University of Batanghari, which is the determination of the quality standards and assessment of an educational institution (higher education) by parties outside of an independent institution. At the opening of the College Institution Accreditation academic manuscript book, it was explained that accreditation is a comprehensive evaluation and assessment process of the college’s commitment to the quality and capacity of implementing Tridarma tertiary institutions, to determine the feasibility of programs and education units. Evaluation and assessment in the framework of institutional accreditation is carried out by an assessor team consisting of experts who understand the nature of university management. Accreditation is an important asset to determine the position of a higher education institution or study program at the level of management competition with higher education institutions and other study programs and is a benchmark for institutions using higher education programs to ensure that graduates are feasible because they are produced from well guarded. Accreditation is very necessary for a standard measure of the quality of education in a tertiary education institution, where each university must be able to improve the quality and competitiveness of its graduates and can guarantee about the teaching and learning process at the university, and as a reference for providing information about the preparation of a college in carrying out the activities of the teaching and learning process according to the standardization provided by the government (the Ministry of National Education) in the process of globalization of education for global competitiveness in the future.